ANALISA DCS (DISTRIBUTED CONTROL SYSTEM) PADA PROSES POLIMERISASI - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
With the development of technology in the industrial market today , many factories - factories require DCS (Distributed Control System) to control the process equipment at the plant. DCS function to read the response is rapid in plant equipment has been fitted with sensors . In this paper will be analyzed the use of DCS in the polymerization process at the factory PT Indorama Synthetics are located in Jatiluhur - Purwakarta , West Java . At PT Indorama Synthetics polymerization process using CENTUM DCS 3000 that can control and monitor every machine connected to the DCS . With the use of DCS , factory PT . Indorama Synthetics can mengontol flow from the tank PTA and EG tank that produces an output flow of 10423 kg / h.